2014
DOI: 10.1089/jwh.2014.4770
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Effectiveness of Compounded Bioidentical Hormone Therapy: A Case Series

Abstract: After the publication of the Women's Health Initiative, attitudes towards management of menopausal symptoms changed dramatically. One alternative that has received much media attention is the use of bioidentical hormone therapy (BHT). The media and celebrity endorsements have promoted a number of misconceptions about the risks and benefits associated with the various forms of BHT. This article will review the available evidence regarding the safety and efficacy of BHT in comparison to conventional hormone ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Consequently, use of unapproved, compounded HT formulations in the USA has risen [37][38][39][40] , reaching an estimated 39 million prescriptions filled annually 41 . Unfortunately, most compounded HT products have not been rigorously studied [42][43][44][45][46] , and many may not provide sufficient endometrial protection or appropriate relief of menopausal VMS, possibly due to non-standardized hormone preparations 41 . Historically, the combination of E2/ P4 in a single oral capsule has been challenging 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, use of unapproved, compounded HT formulations in the USA has risen [37][38][39][40] , reaching an estimated 39 million prescriptions filled annually 41 . Unfortunately, most compounded HT products have not been rigorously studied [42][43][44][45][46] , and many may not provide sufficient endometrial protection or appropriate relief of menopausal VMS, possibly due to non-standardized hormone preparations 41 . Historically, the combination of E2/ P4 in a single oral capsule has been challenging 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen therapy in women shows benefits, although this issue is controversial (Ryan et al 2008); there is, however, no clear evidence of the effect of testosterone substitution in men (Pike et al 2009). Although short-term estrogen therapy could provide benefits to the brain and bones (Daniel et al 2015), breast and endometrial cancer risk after continued exposure has been reported (Davis et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 2011 yılında yayımlanmış gözlemsel kohort çalışmada, aynı coğrafi bölgenin 6 eczanesinde hazırlanmış biyo-özdeş hormon bileşimleriyle 2003-2010 yılları arasında 296 kadın vazomotor semptomları için tedavi edilmiş, duygu durumda belirgin bir iyileşme rapor edilmiştir. Bunun dı-şında, vazomotor semptomlar, kardiyovasküler hastalıklar ve meme kanseri konularında yorum yapılamamıştır.…”
Section: Karşit Görüşunclassified